Development of a Meteorological Database Algorithm for Radio Channel Evaluation - Ajileye, Oluwaseun Olasunmbo (2015)
This study developed an instrumentally and computationally efficient linkage between a meteorological database' and the performance of a radio communication channel by determining the effect of meteorological conditions on the range of frequencies suitable for radio waves under varying meteorological conditions. It also developed an algorithm for evaluating radio channels from meteorological data with a view to predicting the emerging radio communication characteristics.